(untitled) (Global Conference on Medical and Health Sciences, 2026)
Nutrition is a critical component of athletes’ preparation, both for professionals and amateurs. Physical training is associated with substantial energy expenditure, hypoxia, and significant neuropsychological stress, which leads to increased physiological demands for energy and specific nutrients. Meeting these needs through a conventional diet alone is practically impossible; therefore, specially designed nutritional strategies are employed during the training cycle [1, 2, 3]. Athletes eliminate unhealthy foods, monitor their caloric intake, and adhere to other dietary regulations. Weightlifters, more than most, require proper and balanced nutrition. Their needs are unique, characterized by extremely high energy expenditures that demand several thousand kilocalories per day. It is practically impossible to meet these requirements with only two or three meals daily. Therefore, weightlifters consume food multiple times throughout the day according to a structured schedule. However, they also employ certain strategies. Most weightlifters use sports nutrition products, which allow them to intake only the necessary nutrients. [4, 5].